Characterization of the aroma compounds of Millet Huangjiu at different fermentation stages. (1st January 2022) - Ye, Yuting; Wang, Lixia; Zhan, Ping; Tian, Honglei; Liu, Jianshu
Graphical abstract: Highlights: The effects of different fermentation stages on the aroma of MHJ were studied. In the V stage, MHJ had the highest content and the best flavor quality. Esters were the main contributors to MHJ flavor. 14 volatile compounds may cause differences in MHJ flavor at five fermentation stages. Abstract: Millet Huangjiu (MHJ), a type of northern Huangjiu with a long history, has attracted considerable attention in China and East Asia for its unique flavor. To elucidate the changing course of aroma components during the fermentation process of MHJ, 15 MHJ samples prepared at different fermentation stages were assessed by gas chromatography–olfactometry (GC–O) and odor activity value (OAV) coupled with multivariate data analysis. A total of 66 volatile compounds were identified, among which 21 odorant active substances were regarded as the main aroma components (OAVs ≥ 1). The numbers and contents of esters in MHJs accumulated with the extension of fermentation time. Ethanol, ethyl acetate, phenylethyl alcohol and other 7 aromatic substances are the key flavoring agents in the final fermented MHJ. Orthogonal partial least squares-discriminant analysis (OPLS-DA) showed that 14 volatile compounds (formic acid, ethanol, etc.) are supposed to be the key substances that cause significant differences in MHJ flavor at different fermentation stages.